Integrated Use of Satellite Altimetry in the Investigation of the Meteorological, Hydrological, and Hydrodynamic Regime of the Caspian Sea - Sergey A. Lebedev Andrey G. Kostianoy (Terrestrial, Atmospheric and Oceanic Sciences, 2008)

(untitled)
Oscillations in the Caspian Sea level represent the result of mutually related hydrometeorological processes, which proceed not only in the sea catchment area but also far beyond it. The change in the tendency of mean sea level variations that occurred in the mid 1970s, when a long-term level fall was replaced by a rapid and significant rise, represents an important indicator of the changes in the natural regime of the Caspian Sea. Therefore, sea level monitoring and long-term forecast of sea level changes represent an extremely important task. The aim of this publication is to show the results of the application of satellite altimetry methods to the investigation of seasonal and interannual variability of the sea level, wind speed and wave height in different parts of the Caspian Sea and Kara-Bogaz-Gol Bay, and the Volga River level. The work is based on the 1992 - 2006 TOPEX/Poseidon and Jason-1 datasets.